Mechanistic Sequence of Histone Deacetylase Inhibitors and Radiation Treatment: An Overview - Elsie Neo Seane; Shankari Nair; Charlot Vandevoorde; Anna Joubert (MDPI AG, 2024)
Histone deacetylases inhibitors (HDACis) have shown promising therapeutic outcomes in haematological malignancies such as leukaemia, multiple myeloma, and lymphoma, with disappointing results in solid tumours when used as monotherapy. As a result, combination therapies either with radiation or other deoxyribonucleic acid (DNA) damaging agents have been suggested as ideal strategy to improve their efficacy in solid tumours. Numerous in vitro and in vivo studies have demonstrated that HDACis can sensitise malignant cells to both electromagnetic and particle types of radiation by inhibiting DNA damage repair. Although the radiosensitising ability of HDACis has been reported as early as the 1990s, the mechanisms of radiosensitisation are yet to be fully understood. This review brings forth the various protocols used to sequence the administration of radiation and HDACi treatments in the different studies. The possible contribution of these various protocols to the ambiguity that surrounds the mechanisms of radiosensitisation is also highlighted.